A Review on Engineering Design for Enhancing Interfacial Contact in Solid-State Lithium–Sulfur Batteries - Qi, Bingxin; Hong, Xinyue; Jiang, Ying; Shi, Jing; Zhang, Mingrui; Yan, Wen; Lai, Chao (Nano-Micro Letters, 2024)
The utilization of solid-state electrolytes (SSEs) presents a promising solution to the issues of safety concern and shuttle effect in Li–S batteries, which has garnered significant interest recently. However, the high interfacial impedances existing between the SSEs and the electrodes (both lithium anodes and sulfur cathodes) hinder the charge transfer and intensify the uneven deposition of lithium, which ultimately result in insufficient capacity utilization and poor cycling stability. Hence, the reduction of interfacial resistance between SSEs and electrodes is of paramount importance in the pursuit of efficacious solid-state batteries. In this review, we focus on the experimental strategies employed to enhance the interfacial contact between SSEs and electrodes, and summarize recent progresses of their applications in solid-state Li–S batteries. Moreover, the challenges and perspectives of rational interfacial design in practical solid-state Li–S batteries are outlined as well. We expect that this review will provide new insights into the further technique development and practical applications of solid-state lithium batteries. Highlights: 1 The engineering design principles for enhancing interfacial contact between the electrodes (Li anodes and S cathode) and solid-state electrolytes in solid-state Li–S batteries are classified and discussed. 2 Research progresses of experimental strategies for reducing interfacial impedance in solid-state Li–S batteries are summarized. 3 Challenges and future perspectives of rational interfacial strategies in solid-state Li–S batteries are highlighted.